Deconstructing Childhood as a Way to Justice - Lam, Chi-Ming (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2008)
Despite the multiplicity of constructions of childhood in various disciplines, the prevalent view is that children are incompetent in the sense of lacking reason, maturity, or independence. In this paper, I first examine how this dominant view is constructed in the fields of philosophy and psychology, highlighting the perspectives of Plato, Aristotle, John Locke, John Stuart Mill, and Jean Piaget. Then, following Jacques Derrida who conceives justice as a source of meaning for deconstruction, I deconstruct several of the dominant constructions and argue that they do not do children justice. To return justice to childhood, I suggest that childhood should be regarded as a self-contained state with distinctive features that are worthy of consideration in their own right rather than as an incomplete state of incompetence relative to adulthood that is considered a complete state of humans, while adulthood should be regarded as a never-ending process of becoming mature that includes rather than excludes childhood. Moreover, I suggest that both the absolute denial of adult rights to children and the naturalization of childhood in developmental psychology as a biologically determined and culturally universal stage of irrationality should be challenged.